2006
DOI: 10.1002/pon.1023
|View full text |Cite
|
Sign up to set email alerts
|

Active for Life After Cancer: a randomized trial examining a lifestyle physical activity program for prostate cancer patients

Abstract: Results suggest a lifestyle program focusing on cognitive-behavioral skills training alone is insufficient for promoting routine physical activity in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
1
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 68 publications
2
113
1
1
Order By: Relevance
“…However, the lack of decline in physical function and body composition variables noted above 119 suggest that lifestyle guidelines that focus on increasing physical activity might be considered as a minimal dose.…”
Section: Adt: Body Composition and Physical Function Tw Storer Et Al 214mentioning
confidence: 99%
See 3 more Smart Citations
“…However, the lack of decline in physical function and body composition variables noted above 119 suggest that lifestyle guidelines that focus on increasing physical activity might be considered as a minimal dose.…”
Section: Adt: Body Composition and Physical Function Tw Storer Et Al 214mentioning
confidence: 99%
“…25 A number of RCT in men with PCa receiving androgen suppression have shown the value of well-designed exercise training programs. These studies have demonstrated significant improvements in muscle performance, 37,92,117 physical function 37,92,118,119 and body composition 37,120 that occurred after as little as 12 weeks of training. Table 4 summarizes the efficacy of exercise training from five RCT, two uncontrolled trials and one small non-randomized pilot study in men undergoing androgen suppression therapy.…”
Section: Changes With Exercise Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…This can have long-lasting effects; in one intervention study, social support was found to be such a valued part of a group exercise programme for breast cancer survivors that the participants arranged to exercise together weekly following the completion of the intervention (Campbell et al, 2005). However, studies providing physical activity interventions with breast cancer survivors have not all demonstrated the importance of social support -for example, Taylor et al (2006) found that group physical activity education or cognitive-behavioural sessions relating to physical activity did not improve levels of social support. However, the participants in this group did not engage in actual physical activity together and it may be that the collective action element that cancer survivors appear to desire may play an important role in bolstering this support.…”
Section: Individual Versus Group Basedmentioning
confidence: 99%